Zwischenziele und Indikatoren der Geldpolitik - Manfred J. M. Neumann (Kredit und Kapital, 1971)
Interim Objectives and Indicators of Monetary Policy This article deals with various set-ups for determining optimal interim objectives an an optimal indicator for monetary policy. The interim objective and indicator problems were not seen by academic economists for a long time, while monetary policy makers made do with intuitive solutions, the suitability of which could not be systematically checked. The interim objective problem is derived from the general problem of determining an optimal strategy which permits monetary policy instruments to be modified so that desired changes of macroeconomic target magnitudes can be attained. The formal solution presented by Brunner-Meltzer makes it clear that it is rational to concentrate on control of variables in the monetary sector, because in this way the uncertainty as to the system structure can be avoided. The indicator problem consists in determining a monetary variable which permits optimal estimation of the impact of monetary policy on economic activity. With various solution set-ups reasons are adduced to show why the interpretation of monetary policy must be based on an ordinal measuring concept and why simultaneous use of several indicators makes interpretation impossible. Finally it is shown that within the Brunner-Meltzer analytical framework, under certain conditions the extended monetary base can be derived as an optimal indicator of monetary policy.
Keywords: 330